Morphological and anatomical comparison between axes produced by seed and basal branching of Astrocaryum carnosum (Arecaceae) - Rivas, Marinoli (2015)
For the caespitose palm Astrocaryum carnosum are described and compared the foliar morphology and anatomy between axes produced by seed and basal branching in three stages of development; stage 1: with entire leaves; stage 2: with 2–6 pairs of irregular pinnae and stage 3: with 7–21 pairs of pinnae. For each case were considered four morphological and 14 anatomical parameters for phase 1; and 12 morphological and 14 anatomical parameters for phases 2 and 3. Significant differences (p 0.05) were found in the number of leaves, length of petiole, length of lamina, width of basal and middle pinna, thickness of spongy parenchyma, size of non–vascular fibers bundles and stomatal density.